2019
DOI: 10.7202/1060173ar
|View full text |Cite
|
Sign up to set email alerts
|

Traduction automatique et usage linguistique : une analyse de traductions anglais-français réunies en corpus

Abstract: Cet article propose une analyse linguistique d’un corpus de français traduit de façon automatique depuis l’anglais, en comparaison d’un corpus de français original. Deux outils de traduction automatique ont été retenus pour cette étude, l’un générique, grand public et neuronal tandis que l’autre est un outil spécifique, utilisé par une grande organisation internationale et à base de statistiques. Selon la méthodologie de la traductologie de corpus, à travers une analyse quantitative de phénomènes linguistiques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
1
6
0
5
Order By: Relevance
“…In addition to automated methodologies as illustrated in the preceding section, we agree with Loock [1] that a careful manual analysis of examples that remain problematic for MT is of the essence. In this case, we have randomly selected from the news a number of examples of sentences with rich phraseology, which posed a real problem to both Google Translate and DeepL.…”
Section: Phraseology and Nmt: A Closer Look At Problematic Examplessupporting
confidence: 67%
See 2 more Smart Citations
“…In addition to automated methodologies as illustrated in the preceding section, we agree with Loock [1] that a careful manual analysis of examples that remain problematic for MT is of the essence. In this case, we have randomly selected from the news a number of examples of sentences with rich phraseology, which posed a real problem to both Google Translate and DeepL.…”
Section: Phraseology and Nmt: A Closer Look At Problematic Examplessupporting
confidence: 67%
“…Neural machine translation (NMT) is now generally considered as a major breakthrough in machine translation (MT). As pointed out by Loock [1], the growing success of NMT since 2015 is now such that in 2018, and for the first time, more than half of all translation companies and services in Europe reported using MT to some extent. In particular, the results obtained by DeepL with NMT have impressed the general public (as shown by the many newspaper articles on DeepL's web page), as well as language professionals and researchers.…”
Section: Introduction: Lingering Doubts About Neural Machine Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…NMT took a huge leap forward when sequence-to-sequence models were first introduced [18]. So far, it has already achieved excellent performance on a great volume of translations from English into French [12,19] as well as from English into German [20]. MT systems for translating dialectal sentences into their standard language form can be of great benefit as Farhan et al [18] have shown.…”
Section: Evaluation Of Mt Systemmentioning
confidence: 99%
“…Malgré de telles précautions pour produire des textes plus faciles à traduire par la machine, les auteurs reconnaissent que le recours à la post-édition s'avèrera toujours nécessaire et que pour que celle-ci soit efficace, une bonne connaissance des erreurs typiques apparaissant dans les traductions effectuées grâce à des outils de TA est requise. Sur ce sujet, dans la mesure où ces erreurs varient en fonction des langues de travail mais aussi des outils de TA utilisés, les auteurs ne fournissent que très peu d'exemples et ne formulent pas de recommandations concrètes (p. 76-77), ce que le lecteur avide de mise en pratique pourra regretter, d'autant que la littérature scientifique sur le sujet est abondante (par exemple Castilho, Moorkens et al 2017 ;Isabelle, Cherry et al 2017 ;Lapshinova-Koltunski 2015 ;Macketanz, Avramidis et al 2017 ;Loock 2018) et a mis au jour un certain nombre d'erreurs récurrentes ou de biais à corriger lors de la post-édition de textes traduits automatiquement. Un tel développement constituerait d'ailleurs un prolongement naturel de la lecture de l'ouvrage.…”
unclassified